Evaluation of Lhokseumawe City Government Policy in Providing Capital Participation to Regional Company Ie Beusaree Rata - Oktavian Agma, Teuku Fachkri; Alfian, Alfian; Anismar, Anismar; Fazil, Muhammad; A. Rahman, Dahlan (Jurnal Transparansi Publik (JTP), 2024)
PDAM Ie Beusare Rata Lhokseumawe City has not yet carried out an optimal evaluation of the Lhokseumawe City Government's policy in providing capital participation to regional drinking water companies (PDAM). This can be seen from human resources and budgets which are still not optimal. This thesis discusses the Evaluation of Lhokseumawe City Government Policy in Providing Capital Investment to Regional Drinking Water Companies (PDAM) using Dun's theory with indicators of Effectiveness, Efficiency, Adequacy, Equity, Responsiveness and Accuracy. The type of research used is descriptive qualitative with data collection techniques in the form of interviews, documentation and observation. The sampling technique was carried out using purposive sampling. Data sources use primary data, secondary data. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of the research show that the Lhokseumawe City Government's policy evaluation in providing capital participation to regional drinking water companies (PDAM) is still not optimal. This is caused by inadequate human resources and a budget that is not in accordance with the Lhokseumawe City Government Policy in Providing Capital Participation to Regional Drinking Water Companies (PDAM). Recommendations for PDAM Ie Beusare Rata, Lhokseumawe City must improve quality human resources so that performance in providing services to the people of Lhokseumawe City will be more optimal.